2019
DOI: 10.1590/s1413-41522019193972
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microalgae from waste stabilization ponds and evaluation of electroflotation by alternate current for simultaneous biomass separation and cell disruption

Abstract: This work aimed to investigate algal diversity at the genus level in stabilization pond systems treating domestic wastewater and to evaluate the feasibility of an electroflotation by alternate current (EFAC) system for simultaneous microalgae separation and cell disruption. Evaluation of algal diversity showed that the genera Euglena and Chlorella were present in relatively high frequencies in five of the six effluents analyzed. The use of EFAC on an effluent that presented bloom of Chlorella achieved turbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Research conducted in wastewater treatment ponds reports that Chlamydomonas, Chlorella, Euglena, and Scenedesmus spp. are the most commonly occurring microalgal species in tropical, subtropical, and temperate climates (Abis and Mara, 2005;Ahmadi et al, 2005;Crimp et al, 2018;Florentino et al, 2019), with effective capacity to meet ammonium and P removal targets. Nutrient control and recovery from sewage is achieved via algal uptake, which offers a significant benefit over bacteria in that algae accumulate both N and P. Under some environmental/ operational conditions the microalgae perform "luxury P uptake," defined as the uptake of P beyond that required for growth and storage of phosphate within the biomass as PolyP (>1% P dry weight) (Powell et al, 2008).…”
Section: Wastewater Treatment and Phosphate Recyclingmentioning
confidence: 99%
“…Research conducted in wastewater treatment ponds reports that Chlamydomonas, Chlorella, Euglena, and Scenedesmus spp. are the most commonly occurring microalgal species in tropical, subtropical, and temperate climates (Abis and Mara, 2005;Ahmadi et al, 2005;Crimp et al, 2018;Florentino et al, 2019), with effective capacity to meet ammonium and P removal targets. Nutrient control and recovery from sewage is achieved via algal uptake, which offers a significant benefit over bacteria in that algae accumulate both N and P. Under some environmental/ operational conditions the microalgae perform "luxury P uptake," defined as the uptake of P beyond that required for growth and storage of phosphate within the biomass as PolyP (>1% P dry weight) (Powell et al, 2008).…”
Section: Wastewater Treatment and Phosphate Recyclingmentioning
confidence: 99%
“…Other microalgae, including cyanobacterial species, that can be found in wastewater treatment plants are Euglena sp. [63], Micractinium inermum sp. [64], Spirulina maxima, and Synechocystis sp.…”
Section: Phycoremediation As a Tertiary Treatment Of Wastewatermentioning
confidence: 99%
“…(Figure 3). Florentino et al (2019) evaluation of algal diversity in stabilization pond systems treating domestic wastewater showed that the genera Euglena and Chlorella were present in relatively high frequencies in five of the six effluents analyzed. The abundance of Synechocystis sp.…”
Section: Phytoplankton Community Structurementioning
confidence: 99%